Trends in Cancer Incidence in Maputo, Mozambique, 1991–2008 - Lorenzoni, Cesaltina; Vilajeliu, Alba; Carrilho, Carla; Ismail, Mamudo R.; Castillo, Paola; Augusto, Orvalho; García-Basteiro, Alberto L.; Sidat, Mohsin; de Sanjosé, Silvia; Menéndez, Clara; Ordi, Jaume (PLOS ONE, 2015)
Background Very limited information is available regarding the incidence of cancer in sub-Saharan Africa. We analyzed changes in cancer patterns from 1991 to 2008 in Maputo (Mozambique). Methods We calculated the rates of incidence of different cancer sites by sex in the 5-year age-group of the population of Maputo city as well as age-standardized rates (ASRs) and average annual percentage changes (AAPC). Results Over the 18-year study period a total of 12,674 cases of cancer (56.9% females) were registered with an overall increase in the risk of cancer in both sexes. In males, the most common cancers were those of the prostate, Kaposi sarcoma (KS) and the liver. Prostate cancer showed the most dramatic increase over the whole study period (AAPC +11.3%; 95% CI: 9.7–13.0), with an ASR of 61.7 per 105 in 2003–2008. In females, the most frequent cancers were of the uterine cervix, the breast and KS, with the former increasing along the whole study period (AAPC + 4.7%; 95% CI: 3.4–6) with an ASR of 62.0 per 105 in 2003–2008 as well as breast cancer (AAPC +6.5%; 95%CI: 4.3–8.7). Conclusions Overall, the risk of cancer rose in both sexes during the study period, particularly among cancers associated with westernization of lifestyles (prostate, breast), combined with increasingly rising incidences or limited changes in cancers associated with infection and poverty (uterine cervix, liver). Moreover, the burden of AIDS-associated cancers has shown a marked increase.